BIOREMEDIATION OF HEAVY METAL CONTAMINATED SOILS AND ITS IMPACT ON SPINACH GROWTH AND PHYSIOLOGICAL HEALTH - Jyoti; Nanda, Abhijeeta (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the potential of microbial bioremediation to improve soil quality and enhance spinach (Spinacia oleracea) growth in soils contaminated with heavy metals. Soil samples were collected from heavily contaminated sites in Haryana, India, and treated with native microbial consortia and engineered microbial strains. The impact of bioremediation on spinach growth was assessed by measuring growth parameters, chlorophyll content, and antioxidant enzyme activities. Results showed significant improvements in shoot length, root length, total biomass, chlorophyll content, and antioxidant enzyme activities in spinach plants grown in remediated soils compared to control soils. This research suggests that microbial bioremediation can be a sustainable solution for restoring contaminated soils and promoting healthier crop growth.